ENTRELAÇANDO SABERES E NARRATIVAS: FORMAÇÃO DE PROFESSORAS/ES E LIDERANÇAS QUILOMBOLAS EM CONCEIÇÃO DA BARRA/ES - Miranda, Noelia da Silva (2020)
We sought to study the emancipatory possibilities for the formation of teachers and quilombola leaders. The research was carried out in the territory of Sapê do Norte in Conceição da Barra, in the state of Espírito Santo, Brazil, spaces previously organiz